2022
DOI: 10.1111/jfpp.17079
|View full text |Cite
|
Sign up to set email alerts
|

Quality characteristics and microstructure of boiled snail fillet meat

Abstract: In order to investigate the quality characteristics of boiled snail fillets, the microstructure of fillets of farmed Cornu aspersum maximum was studied for the first time. The cylindrical specific mid‐posterior region of snail fillets was used for hardness measurement with geometry 6 mm diameter and 6 mm height. Histological analysis proved that this region was uniform and hardness measurements on this part could show the difference between boiled farmed and wild species without variations from environmental a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 45 publications
3
1
0
Order By: Relevance
“…In the study of Djikeng et al (2022), boiling with water or steaming for 24 min followed by frying consider-ably increased the protein content of snail Archachatina marginata meat. The studies of Kougiagka et al (2022) showed that the level of protein in boiled meat of the snail species Cornu aspersum was similar to that found in our research. In chicken breast as a result of heat treatment the protein content increased by 27.4% (Cupisti et al, 2006), while in beef steak after frying this content increased by 52.0-55% (Brugiapaglia and Destefanis, 2012;Cupisti et al, 2006).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the study of Djikeng et al (2022), boiling with water or steaming for 24 min followed by frying consider-ably increased the protein content of snail Archachatina marginata meat. The studies of Kougiagka et al (2022) showed that the level of protein in boiled meat of the snail species Cornu aspersum was similar to that found in our research. In chicken breast as a result of heat treatment the protein content increased by 27.4% (Cupisti et al, 2006), while in beef steak after frying this content increased by 52.0-55% (Brugiapaglia and Destefanis, 2012;Cupisti et al, 2006).…”
Section: Discussionsupporting
confidence: 90%
“…Their water holding capacity decreases and a partial loss of fluid from the meat occurs (Hultin, 1985). This leads to an increase of the dry matter content, as observed in our research, especially in the case of the foot of snails Cornu aspersum aspersum where this parameter increased by about 1/4 up to 23.18%, only slightly lower than 25.13% that was found by Kougiagka et al (2022) in boiled fillets of the same species. The same tendency has also been found in the heat treatment of meat of other animal species.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Steam cooking marinated pork chops under high pressure, examined by O'Neill et al (2019a), showed improved physicochemical (cook loss, moisture content, WBSF, and n-6:n-3 PUFA ratio) and sensory (texture, tenderness, juiciness, and OSA) attributes. Kougiagka et al (2022) examined the qualitative attributes of boiled snail fillets marinated with acids, salt, different oils, and spices. The hardness of the cylindrical mid-posterior region of the boiled snail fillet signaled the presence of the flesh's fat and carbohydrate contents.…”
Section: Boiling/steam Cookingmentioning
confidence: 99%